2022
DOI: 10.1039/d2em00166g
|View full text |Cite
|
Sign up to set email alerts
|

Use and release of per- and polyfluoroalkyl substances (PFASs) in consumer food packaging in U.S. and Canada

Abstract: PFASs used in food packaging have the potential to contaminate the environment and numerous parts of the waste stream.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…At a leaching rate assumed to be 100%, the emissions of PFAS from sanitary pads and infant’s paper diapers were estimated to be 2.58 and 322 kg per year, a little different from the estimated PFAS emission (37 kg per year) from facemasks at the same 100% leaching rate . The releases of PFAS from food packaging to the environment were estimated in the U.S. and Canada with a total of 2270 and 260 kg per year, respectively . Specifically, the PFAS emissions were estimated to be, in kg per year, 0.822 (Σ 9 PFSAs), 0.5445 (Σ 9 PFCAs), and 0.0633 (Σ 3 PFPAs) from sanitary pads and from infant’s paper diapers were 14.7, 204 and 30.9 kg per year.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At a leaching rate assumed to be 100%, the emissions of PFAS from sanitary pads and infant’s paper diapers were estimated to be 2.58 and 322 kg per year, a little different from the estimated PFAS emission (37 kg per year) from facemasks at the same 100% leaching rate . The releases of PFAS from food packaging to the environment were estimated in the U.S. and Canada with a total of 2270 and 260 kg per year, respectively . Specifically, the PFAS emissions were estimated to be, in kg per year, 0.822 (Σ 9 PFSAs), 0.5445 (Σ 9 PFCAs), and 0.0633 (Σ 3 PFPAs) from sanitary pads and from infant’s paper diapers were 14.7, 204 and 30.9 kg per year.…”
Section: Resultsmentioning
confidence: 99%
“…68 The releases of PFAS from food packaging to the environment were estimated in the U.S. and Canada with a total of 2270 and 260 kg per year, respectively. 69 Specifically, the PFAS emissions were estimated to be, in kg per year, 0.822 (Σ 9 PFSAs), 0.5445 (Σ 9 PFCAs), and 0.0633 (Σ 3 PFPAs) from sanitary pads and from infant's paper diapers were 14.7, 204 and 30.9 kg per year. This result indicated that PFAS emissions through infant's paper diapers may pose a greater risk to the environment than sanitary pads, the reason being that, in addition to the higher PFAS concentration measured in the diapers, it is possible that the top layer of the diapers has a larger volume and weight than that of the sanitary pads.…”
Section: Significance Of Pfas Exposure In Humans Through Personalmentioning
confidence: 99%
“…Electrochemical fluorination (ECF)-based neutral PFAS were measured in ambient air near landfills in prior studies, but were less than LOD in the LFG samples in the present study (Table ). A larger-scale study is required to better understand if the lack of ECF-based PFAS is due to landfill age/cell closure, given that the production of ECF-based neutral PFAS ceased in the early 2000s ,,, and/or due to the proximity of landfill to ECF industries. , Sources of FTOHs may include degradation of FT-based fluoropolymers, ,, side-chain fluorinated polymers, ,, or from residual FTOHs in consumer products, ,, as well as in side-chain fluorinated polymers; , meanwhile, FTAcs are known precursors to FTOHs. , To the best of our knowledge, this is the first report of 12:2 FTO associated with landfills. The 12:2 FTO was previously measured in ambient air, not associated with landfills. Five other target PFAS were detected at less than LOQ, but greater than LOD, including 6:2 FTI (Table ), which was previously measured in ambient air surrounding a landfill …”
Section: Resultsmentioning
confidence: 99%
“…5,6 Consumer product samples Similarly, m-XRF map images were obtained for selected consumer products, as they were reported to emit substances of health and environmental concern. 45 One sample was taken from a food contact material (Paper1), two textile samples were taken from used outdoor jackets (Textile1 and Textile2) and one sample was taken from a 'non-stick' labelled permanent baking sheet (Sheet1). Subsequently, all samples were investigated via uorine K-edge m-XANES spectroscopy (Fig.…”
Section: Environmental Samplesmentioning
confidence: 99%